Field trip - Paulsen, Gary; Paulsen, Jim (Wendy Lamb Books, 2015)
Ben has been invited to try out for a special hockey academy. But Dad wants Ben to catch up to the school field trip instead. So Ben, Dad, and their dogs, Atticus and Conor, jump into their truck. Ben concocts a secret plan to make the tryout, but Atticus and Conor are on to him. Dad's new apprentice, Brig, and Ben's twin classmates, Jacob and Charlotte, are along for the ride.